2015
DOI: 10.1371/journal.pone.0142439
|View full text |Cite|
|
Sign up to set email alerts
|

Extraction and Identification of the Pigment in the Adductor Muscle Scar of Pacific Oyster Crassostrea gigas

Abstract: In this study, UV (ultraviolet) and IR (infrared radiation) spectral analysis were integrated to identify the pigment in the adductor muscle scar of the Pacific oyster Crassostrea gigas. The pigment was extracted from the adductor muscle scars of cleaned oyster shells that were pulverized, hydrolyzed in hot hydrochloric acid, purified with diethyl ether, and dissolved in 0.01 mL/L NaOH. The maximum absorption of the pigment in the UV absorption spectrum within the range of 190–500 nm was observed between 210–2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 21 publications
0
26
0
Order By: Relevance
“…In previous Raman studies of molluscan shells, black and brown pigments have been attributed to polyenes, but other studies using high‐performance liquid chromatography, mass spectrometry, or spectral analysis have shown that these shell colours can also be due to melanins or tetrapyrroles . The brown tetrapyrrole protoporphyrin IX has been found in the pteriomorph Argopecten sp ., and Raman studies showed that it exhibits Raman peaks attributable to C═C bonds at 1,619, 1,585, and 1,339 cm −1 ; C–C deformation at 1,255 cm −1 ; and C–C and C–H 3 rocking at 970 cm −1 .…”
Section: Resultsmentioning
confidence: 62%
“…In previous Raman studies of molluscan shells, black and brown pigments have been attributed to polyenes, but other studies using high‐performance liquid chromatography, mass spectrometry, or spectral analysis have shown that these shell colours can also be due to melanins or tetrapyrroles . The brown tetrapyrrole protoporphyrin IX has been found in the pteriomorph Argopecten sp ., and Raman studies showed that it exhibits Raman peaks attributable to C═C bonds at 1,619, 1,585, and 1,339 cm −1 ; C–C deformation at 1,255 cm −1 ; and C–C and C–H 3 rocking at 970 cm −1 .…”
Section: Resultsmentioning
confidence: 62%
“…Therefore, the formation and development of AM has a very important effect on the growth and diet of oysters. On the other hand, AM produces large amounts of melanin, and it is reported that the more melanin in the shell, the higher the dry weight of oysters (Yu et al 2017;Hao et al 2015;Xiao yan et al 2003). Melanin removes free radicals and reduces damage to AM, which allows AM to open larger shells and filter out more algae to speed up growth.…”
Section: Discussionmentioning
confidence: 99%
“…It has been found that the pigmented adductor muscle scar to which the “black muscle” was attached contained melanin (Hao et al, 2015 ) and a tyrosinase gene was involved in melanin production (Kumar et al, 2011 ). So, the results of this study suggests that these two tyrosinase genes may play an important role in melanin deposition on adductor muscle scar in C. gigas .…”
Section: Discussionmentioning
confidence: 99%
“…Current research into the pigmentation of mollusks is mainly focused on carotenoids in the shell and soft body (Li et al, 2010 ; Zheng et al, 2010 , 2012 ; Maoka, 2011 ; Maoka et al, 2014 ; Liu et al, 2015 ; Williams, 2017 ), which have roles in quenching singlet oxygen species, eliminating free radicals, acting as antioxidants, and supporting the immune system (Rao and Rao, 2007 ; Maiani et al, 2009 ). Melanin has a similar biological function as carotenoids (Kollias et al, 1991 ; Sharma et al, 2002 ), and it has been confirmed that the black pigment in the soft body, outer surface of the shell, and adductor muscle scar of oysters is melanin (Hao et al, 2015 ; Yu et al, 2015 ; Williams, 2017 ).…”
Section: Introductionmentioning
confidence: 93%